Abu Hafs Al-Hawzani Al-Ishbili Al-Andalusi: His Biography and Literary Output - Matroud, Dr. Arif Abdel-Karim; Hamid, Woroud Muhammad (Thi Qar Arts Journal, 2024)
There are many studies of Andalusian literature. Here, we wanted to shed light on an Andalusian personality who had no independence in interest and study. The sources and references in Andalusian literature spoke clearly about her. This study illuminated her life story and all aspects leading up to her demise, attributing to her a unique scientific, religious, political, and social standing that is unparalleled globally. The era of the kings of the Andalusian sects, and we found historical and literary glorification for it through what the sources have proven, and we have proven that it had bright news and effects that called for paying attention to it, paying attention to it, and knowing it more precisely. Therefore, we believe that this work is an academic document that attests to Al-Hawzani’s honorable biography and his distinguished literary production.